Quer conhecer a Finlândia? Vá a penedo! Uma proposta de roteiro turístico cultural - Rocha, Diego Uliano (2019)
Penedo is a neighborhood belonging to the municipality of Itatiaia, located in the state of Rio de Janeiro. The arrival of Finnish immigrants in the early twentieth century was a historical fact that changed the course of this former coffee farm in the south of the state. The place became the home of the Finns in Brazil. It, in turn, contributed to the change of plans of the group: from agricultural colony to tourist destination. Agriculture, designed to be the dominant economic activity, did not prosper, given the conditions of the land. The reception of visitors, provided as a supplementary means of income, became the main path to survival. Thus, the Finns began to market, through tourism, the finlanidade. It is a kind of "aura" impregnated in the products and services produced in the place. The finlanidade is disguised under of the idea of blood and territorial nationality but, in fact, are characteristics invented by the group, over time, to differentiate themselves from the others. The increase of the tourist flow gave appropriation of the finlanidade by other people not belonging to the circle of the immigrants. Disputes and conflicts arose around the forms of expression of the finlanidade, in its tourist commercialization. It is believed that this process has led to the formulation of multiple versions on finlanidade, each in its own way. It is assumed that one of these narratives stood out in relation to the others, leading to the existence of a unique story about finland in the tourist scene. By means of these questions, the present work tried to formulate a biography of the finlanidade until the present time. This research contributes to the knowledge about the immigrant group, as well as to the processes of mobilization and existing identity disputes related to the tourist activity, throughout the construction of the tourist destination. The verification of the existence of other narratives was made by traces of written memories, found in books produced by immigrants and spoken, taken through interviews. Parallel to this process was used information contained in periodicals in order to enrich the scenario told by written and spoken statements. As a result of the research, a map was developed for the identification of these places, placed in this work as a proposal of a cultural touristic route where the diverse voices about the past and present of the Finnish immigration in Penedo are valued.